2022
DOI: 10.3390/batteries9010001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sample Interval on the Parameter Identification Results of RC Equivalent Circuit Models of Li-ion Battery: An Investigation Based on HPPC Test Data

Abstract: The validity of the equivalent circuit model (ECM), which is crucial for the development of lithium-ion batteries (LIBs) and state evaluation, is primarily dependent on the precision of the findings of parameter identification. In this study, the commonly used first-order RC (1-RC) circuit and second-order RC (2-RC) circuit models were selected for parameter identification. A time series of voltage with different sample intervals were used for function fitting based on the least square method, which were extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Some of the common examples of the ANN are the BP network and radial basis network. Hence, based on these three types of modelling, the BMS can be designed for the EVs in the market [25], [26]. Further, one element of the circuit-oriented battery model is shown in Figure 3.…”
Section: Battery Modelling Systems For Electric Vehiclesmentioning
confidence: 99%
“…Some of the common examples of the ANN are the BP network and radial basis network. Hence, based on these three types of modelling, the BMS can be designed for the EVs in the market [25], [26]. Further, one element of the circuit-oriented battery model is shown in Figure 3.…”
Section: Battery Modelling Systems For Electric Vehiclesmentioning
confidence: 99%
“…They found that the three factors can significantly affect the accuracy of parameter identification. Zhang et al [32] found that setting different sample intervals during the HPPC experiment will impact the parameter identification results. However, there is still some room for further research to explore the impact of different HPPC experimental parameter combinations on battery modeling accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the widely used method is the model-based battery SOH prediction method, which estimates the SOH of LIBs by combining an electrochemical model or an equivalent circuit model with established state-space equations. Examples of these models include the second-order RC equivalent circuit model [10], fractional-order equivalent circuit model [11], and the core-buffer equivalent circuit model [12]. In recent years, with the widespread application of probability and statistical theory and the rise of big data, the machine learning model has also been applied in the field of LIB SOH prediction.…”
Section: Introductionmentioning
confidence: 99%